1973
DOI: 10.1002/bjs.1800601011
|View full text |Cite
|
Sign up to set email alerts
|

A review of 15 years' experience in the use of sclerotherapy in the control of acute haemorrhage from oesophageal varices

Abstract: The results of 15 years of sclerotherapy for acute variceal haemorrhage are reviewed retrospectively. One hundred and seventeen patients with portal hypertension received a total of 217 injections. Haemorrhage was controlled in 93 per cent of admissions. The mortality per injection was under 12 per cent, and the total admission mortality was 18 per cent. Even where a subsequent shunt was impracticable, sclerotherapy provided useful palliation with few serious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
2

Year Published

1980
1980
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(62 citation statements)
references
References 7 publications
0
60
0
2
Order By: Relevance
“…The management of children with portal vein thrombosis has undergone many changes due to an improved understanding of the natural history and pathophysiology ofthis disorder.3-5 8 Injection sclerotherapy, first initially reported by Crafoord and Frenckner30 in the late 1930s, has re-emerged and established itself in many centres as the most effective therapeutic modality currently available to control variceal haemorrhage in patients who threaten to continue bleeding after a trial period of conservative management.14 [18][19][20][21][22][23] Despite these trends, however, surgery will remain important for the subset of patients who experience ongoing life threatening haemorrhage and for those in whom endoscopic facilities and expertise prove inaccessible or unavailable.5 15-17 25 26 Data on the long term results of surgical intervention in such children with portal vein thrombosis remain an issue for continued debate. Concerns about the threats of portosystemic encephalopathy, shunt thrombosis, rebleeding, and sepsis after splenectomy dominate some of the issues which are addressed in this study.2-10 12 14-17 25 27 Portosystemic shunts were performed as primary procedures in nine patients in this series with a 56% success rate.…”
Section: Discussionmentioning
confidence: 99%
“…The management of children with portal vein thrombosis has undergone many changes due to an improved understanding of the natural history and pathophysiology ofthis disorder.3-5 8 Injection sclerotherapy, first initially reported by Crafoord and Frenckner30 in the late 1930s, has re-emerged and established itself in many centres as the most effective therapeutic modality currently available to control variceal haemorrhage in patients who threaten to continue bleeding after a trial period of conservative management.14 [18][19][20][21][22][23] Despite these trends, however, surgery will remain important for the subset of patients who experience ongoing life threatening haemorrhage and for those in whom endoscopic facilities and expertise prove inaccessible or unavailable.5 15-17 25 26 Data on the long term results of surgical intervention in such children with portal vein thrombosis remain an issue for continued debate. Concerns about the threats of portosystemic encephalopathy, shunt thrombosis, rebleeding, and sepsis after splenectomy dominate some of the issues which are addressed in this study.2-10 12 14-17 25 27 Portosystemic shunts were performed as primary procedures in nine patients in this series with a 56% success rate.…”
Section: Discussionmentioning
confidence: 99%
“…1968: Hashoffer, 1970Pinel et al. 1971;Marchai, 1972: John ston andRodgers, 1973). Thus, the longitudinal muscle cells described from oesophageal veins by several authors [Spanner.…”
Section: Discussionmentioning
confidence: 99%
“…1971;Johnston and Rodgers, 1973). These authors reported that only a small quantity of scle rosing substance can be injected into the esophageal vari ces.…”
Section: Discussionmentioning
confidence: 99%